2004
DOI: 10.2136/sssaj2004.2920
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Dissolved Organic Carbon and Nitrogen in Soils of a Weathering Chronosequence

Abstract: Adsorption of DOM by soil has been implicated as a very important factor in controlling the loss of DOM Leaching of dissolved organic matter (DOM) and the associated from ecosystems in stream water (McDowell and Wood, nutrient elements can be a significant form of loss from developing 1984; Nelson et al., 1993; Qualls et al., 2002). Several ecosystems. We studied how the adsorption of dissolved organic C (DOC) and N (DON) changes during soil development and deter-authors have found positive correlations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 41 publications
4
57
1
Order By: Relevance
“…Actually, adsorption of dissolved organic matter depends on molecular weight, acidic group and aromatic structure (Kaiser and Zech, 2000). The adsorption of DOC and DON also depends on their respective concentrations in the draining water (Lilienfein et al, 2004). According to Lilienfein et al (2004), at low initial concentrations in soil solution, the soil releases potentially more dissolved organic matter (DOM) than at higher concentrations for which it is more likely to retain these substances.…”
Section: Dissolved Organic Carbon (Doc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, adsorption of dissolved organic matter depends on molecular weight, acidic group and aromatic structure (Kaiser and Zech, 2000). The adsorption of DOC and DON also depends on their respective concentrations in the draining water (Lilienfein et al, 2004). According to Lilienfein et al (2004), at low initial concentrations in soil solution, the soil releases potentially more dissolved organic matter (DOM) than at higher concentrations for which it is more likely to retain these substances.…”
Section: Dissolved Organic Carbon (Doc)mentioning
confidence: 99%
“…The adsorption of DOC and DON also depends on their respective concentrations in the draining water (Lilienfein et al, 2004). According to Lilienfein et al (2004), at low initial concentrations in soil solution, the soil releases potentially more dissolved organic matter (DOM) than at higher concentrations for which it is more likely to retain these substances. Meanwhile, Lilienfein et al (2004) also state that adsorption mechanisms of both species are controlled by similar factors.…”
Section: Dissolved Organic Carbon (Doc)mentioning
confidence: 99%
See 1 more Smart Citation
“…If the affinity of soil particles for DOC (i.e., the partition coefficient) decreases as the concentration of sorbed DOC increases (i.e., a Langmuir adsorption isotherm [Sparks 1995]), higher concentrations of DOC in soil solutions would lead to proportionally less adsorption on soil. Though some studies on DOC adsorption have demonstrated a linear response of DOC sorption to increasing solution concentration, notably at much lower DOC concentrations than those in CWD leachate (Nodvin et al 1986;Kaiser et al 1996;Kaiser et al 2000), others have shown a Langmuir-type response (van Hees et al 2003;Lilienfein et al 2004). Microbial degradation of DOC may also be proportionally lower in soil with higher concentrations of DOC, due to a shift in limitation from C to N or some other element.…”
Section: Dissolved Organic Mattermentioning
confidence: 99%
“…Also in the field, their importance for long-term OM stabilization has been affirmed by correlations found between the contents of OC and mineral phase properties. For example, in andic soils, poorly crystalline aluminosilicates (allophane, imogolite-type minerals) were shown to account for the sorption and preservation of OM (Torn et al 1997;Lilienfein et al 2004). In temperate, non-allophanic soils of varying phyllosilicate composition, Wiseman and Pu¨ttmann (2005) observed that C storage was largely a function of the contents of Fe and Al (hydr)oxides.…”
Section: Introductionmentioning
confidence: 99%